An Ocean of Tears: Decentreing Institutional Marginalisation of Pacific Arts Agency - Tu'u, Louise Talamoni (Auckland University of Technology, 2017)
This exegesis explores three key projects that form part of my recent performative practice: An Anthem of Hope, Screenshot and the upcoming Magdalena of Mangere in which group dynamics—which bring people together in spaces of difficulty, resistance, embarrassment, game-playing or distance—are explored. These performance works commonly test institutional boundaries, cultural identities and relationships. The project explores ways in which audiences, including frequently the host gallery and the artist herself - Louise Tu’u - may be drawn in, or induced into social relationships that play out relations of humour and dis-ease. In attending to these relationships, the project aims to develop fluid methods of engagement or intervention in the politics of marginalised communities.
Keywords: Pasifika performance; Fa'alavelave; Wroughting; Female body; Institutional critique; Fiapoto; Fa'amatala; Faitatala; Physics Room; Mangere Arts Centre; Papakura Art Gallery; South Auckland; Epeli Hau'ofa; Auckland; Civic participation